Майбутній менеджер туризму у процесі формування німецькомовної комунікативної компетентності - Окопна, Яна Володимирівна (КНЛУ, 2014)
У роботі подаються основні вимоги до фахівців сфери туризму та особливості туристської освіти у вищих навчальних закладах. Визначено сутність і зміст компонентів готовності до професійної діяльності майбутніх фахівців та охарактеризовано критерії, показники і рівні їх прояву. The basic requirements for the specialists in tourism sphere and peculiarities of tourist foreign language education in high schools are given in this work. The essence and contents of components readiness for future specialists’ professional activity in international tourism are determined and criteria, indexes and levels of their display are characterized. The model of the students training system of tourism faculty for sport health activity, psychological and pedagogical conditions of its foreign language realization, and also program and methods of the formation of future specialists’ readiness to the professional activity in sport-health tourism are offered.
Keywords: діалогічне мовлення; dialogical speech; професійно орієнтоване навчання; job-related training; фахова діяльність; professional activities; кафедра іноземних мов професійного спрямування